Knowledge, attitude and practice on breastfeeding in Klang, Malaysia - KL, Tan (IIUM Medical Journal Malaysia, 2009)
Introduction: In Klang, a district in the state of Selangor in Peninsular Malaysia, the effects of westernization and urbanization in recent years have had an impact on infant feeding. The objective of this study was to evaluate the practice, knowledge and attitude to breastfeeding and to assess factors associated with breastfeeding among women in Klang, Malaysia. Materials & Methods: A cross-sectional study was carried out between June and October 2006 involving 220 women with infants aged six months from two randomly selected health clinics were selected and interviewed. Data on socio-demographic, infant factors, infant feeding in the first six months of life, knowledge and attitude towards breastfeeding were collected. Results: Exclusive breastfeeding was reported by 32.8%, mixed feeding was reported by 14.5% and infant formula feeding was reported by 52.7% of the respondents. Chinese women were more likely not to practice exclusive breastfeeding compared to Malay women (odds ratio 18.27, 95% CI: 3.95, 84.54) while working women were more likely not to practice exclusive breastfeeding compared to non working women (odds ratio 3.75, 95% CI: 1.64, 8.55). Positive association with not exclusive breastfeeding included women with high household income and women with male infants. Malaysian women had a positive attitude but work place and short maternity leave had a negative impact on breastfeeding. Conclusion: Women of Chinese ethnicity, working, from high family income and with male infants were less likely to exclusively breastfeed. Adopting facilitatory measures at hospitals and work place could increase the rate of exclusive breastfeeding.